Pengaruh Keamanan dan Kepercayaan Terhadap Keputusan Pembelian pada E-Commerce Shopee di Surabaya - Bima Prasetya, Miftaqul; Nur Achmad, Andrean; Rachma Kamila, Edita (PENG: Jurnal Ekonomi dan Manajemen, 2025)
This study aims to determine the influence of security and trust on purchase decisions on Shopee e-commerce in students in the Surabaya area and in the Sidoarjo area. The analysis technique used is a quantitative method using SPSS version 25.0. The sampling technique in this study is a purposive sampling technique. This study uses descriptive statistical analysis and multiple linear regression. The sample in this study was 95 respondents consisting of students from two private universities in Surabaya and in Sidoarjo. The results of this study show that security and trust have a positive and significant effect on purchase decisions on Shopee e-commerce for students in Surabaya and in Sidoarjo either partially or individually and simultaneously or together.